Avaliação do potencial biológico de extratos hidroetanólicos de Astronium sp incorporados ou não em sistemas nanoestruturados: in vitro e in vivo: in vitro e in vivo - Negri, Kamila Maria Silveira [UNESP] (2015)
The medicinal plants are of great importance in view of the use of the active substances as prototypes for drug development and as a source of pharmaceutical raw materials. In this context, researchers have been the need to assess the biological potential of the various plant species of the Brazilian Cerrado. Among these plants is the Astronium sp with the species A. urundeuva (aroeira-do-sertão), A. graveolens (Guaritá) and A. fraxinifolium (Gonçalo-alves), popularly used as anti-inflammatory, antimicrobial, anti-ulcerogenic and healing. The use of nanotechnology is the most modern tool to enhance the biological activity of natural products, among nanostructured systems used there are the microemulsion. In order to evaluate the biological potential of the species of Astronium sp used the test determination of phenols and flavonoids, antioxidant, anti-angiogenic activity, incorporating extracts in nanostructured systems, healing activity, anti-Helicobacter pylori in vivo, in vitro antimicrobial and cytotoxic. The minimum inhibitory concentration (MIC) of plant extracts (from 1000 to 7.81 μg/mL) was determined by the microdilution against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, ATCC 19196 Salmonella setubal, Helicobacter pylori ATCC 43504 and Candida albicans ATCC 18804. As control was used amoxicillin (100 μg/mL) for H. pylori; ampicillin (50 μg/mL) for the remaining bacteria and amphotericin B (32 μg/mL) and fluconazole (256 μg/mL) for C. albicans, and 0.01% resazurin (bacteria) and chloride 2,3,5-triphenyltetrazolium 2% - TTC (yeast) used as revealing. The extracts were incorporated into two systems: System 1 [10% oil phase (cholesterol), 10% surfactant (Brij 98® and soybean phosphatidylcholine - 2: 1) and 80% aqueous phase (pH = 7.4 phosphate buffer)]; System 2 [10% oil phase (cholesterol), 10% surfactant (Brij 58® and soybean ...